Air pollution control using hybrid system / Mohd Azim Shah Mohd Khalid - Mohd Khalid, Mohd Azim Shah (Faculty of Mechanical Engineering, 2003)
The environment possesses the natural self-cleansing processes such as dispersion, gravitational settling, flocculation, absorption (which involved scavenging and washout), rainout and adsorption that maintain the stability and balance of the ecosystem. These great natural mechanisms lessen the amount of pollutants from being concentrated at one place that might be hazardous to the livings that settled in a particular ecosystem. However, the effectiveness of the mechanism is getting lower and lower, day by day, in the recent times since the amount of pollutants which are mostly produced by human activities are rapidly increasing. The overwhelming emission of exhaust gases from the industries can cause serious problems to the ecosystem where it damages the plants, reduces distance of visibility, corrodes the surfaces of buildings and increases the number of human respiratory problems. As the solution, actions have to be made to reduce the amount of particulates and gaseous emissions by implementing control procedures and installing control mechanisms. However, since there are no technologies that can ensure total control of the pollution, low-level emissions are still released into the atmosphere inevitably and only the natural atmospheric cleansing mechanism can remove them.